IPO patterns in Euronext after the global financial crisis of 2007-2008 - Silva, Nuno (2020)
This paper investigates the pricing patterns of 161 IPOs that occurred in 2009-2017 in the Euronext markets of Amsterdam, Brussels, Lisbon, and Paris. Across all the IPOs, we find a first-day raw return of 1.4% and an industry-adjusted return of 1.2%. After one year, the average raw returns are slightly higher, around 4.5%, and the average adjusted returns are negative, around -2.7%. These first-day returns are lower whilst long-run returns are higher than those reported in other studies, most notably in those that use periods that overlap our sample Healthcare is the industry that presents a higher initial underpricing (2.3% industry-adjusted return), whilst the Technology industry presents the higher year underperformance (-29.5% industry-adjusted return). Mainly, results are in line with the market conditions and investor sentiment hypotheses according to which, when market conditions are bad (crises), uninformed investors are not so active and optimistic in the IPO market, hence initial underpricing and subsequent underperformance tend to be lower.